Phytochemical Profiling and Bioactive Potential of Momordica Balsamina Seed Extracts for Antidiabetic Activity and Antioxidant Potential - Khatoon, Razia; Ghani, Mujtaba; Shahzad, Saira; Siddiqa, Maleeka; Azmat, Muhammad; Zafar, Imran; Shafiq, Shaista (Indus Journal of Bioscience Research, 2025)
This study evaluates the bioactive potential of Momordica balsamina through phytochemical screening, GC-MS profiling, antidiabetic activity assessment, and antioxidant analysis. Phytochemical screening revealed a diverse profile of secondary metabolites, with alkaloids (+++), flavonoids (+++), and glycosides (+++) being the most abundant, particularly in ethyl acetate and methanolic extracts. GC-MS analysis further identified key bioactive compounds, with vicine (80%, RT 4 min, peak area 202.25%), a potent antioxidant and antidiabetic glycoside, emerging as the most abundant. This was followed by charantin (167.56%, RT 5.5 min), a well-known hypoglycemic agent, and triterpenoids (17.34%, RT 6.9 min), recognized for their anti-inflammatory and anticancer properties.The antidiabetic potential of Momordica balsamina was assessed through α-amylase inhibition, where the distilled water leaf extract exhibited the highest inhibition rate (82.63 ± 1.55%), closely approaching that of gallic acid (91.96 ± 1.45%). Comparatively, the ethanolic seed extract showed a notable inhibition rate (69.96 ± 1.55%), further demonstrating the plant’s efficacy in diabetes management. Additionally, the antioxidant capacity was evaluated using the FRAP assay, which indicated strong ferric ion-reducing activity. Among the extracts, the methanolic extract demonstrated the highest reducing ability, reinforcing its potential to combat oxidative stress. The study highlights Momordica balsamina’s therapeutic potential, especially in diabetes management and oxidative stress reduction. Ethyl acetate and distilled water extracts exhibited high phytochemical content, with key bioactive compounds like vicine, charantin, and triterpenoids reinforcing its pharmacological importance. The strong efficacy of the distilled water extract suggests that simple extraction methods can yield potent bioactive compounds for herbal formulations. These findings validate its traditional medicinal use and support further in vivo studies and clinical evaluations to explore its full therapeutic potential.